Risk Measures and Attitudes - Biagini, Francesca; Richter, Andreas; Schlesinger, Harris; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Risk has been described in the past by a simple measure, such as the variance, and risk attitude is often considered simply a degree of risk aversion. However, this viewpoint is usually not sufficient. Risk Measures and Attitudes collects contributions which illustrate how modern approaches to both risk measures and risk attitudes are inevitably intertwined. The settings under which this is discussed include portfolio choice, mitigating credit risk and comparing risky alternatives. This book will be a useful study aid for practitioners, students and researchers of actuarial science and risk management.
Weak Closedness of Monotone Sets of Lotteries and Robust Representation of Risk Preferences -- Multivariate Concave and Convex Stochastic Dominance -- Reliable Quantification and Efficient Estimation of Credit Risk -- Diffusion-based models for financial markets without martingale measures.
Keywords: Actuarial science; Economics, Mathematical .; Applied mathematics; Engineering mathematics; Probabilities; Actuarial Sciences; Quantitative Finance; Applications of Mathematics; Probability Theory and Stochastic Processes